ANALISIS MANAJEMEN RISIKO TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK ISO 31000 PADA UNIT PEGADAIAN CABANG (UPC) RATAHAN - Turambi, Cindy Claudya; Rudianto, Christ (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
This research aims to analyze and minimize the impact of the risks that will occur at UPC Pegadaian Ratahan. Risk management analysis in this research uses the ISO 31000 framework guidelines which consist of the risk identification, risk analysis, risk evaluation, and risk treatment. The results found there are 14 risks that can disrupt business processes, but of the 14 risks there are no risks with a high risk level, there are 10 medium risk level risks, and 4 low risk level risks. To reduce the impact of the risks that have been identified in this research, risk treatment strategies are applied, including Mitigating risks (Fire, Abuse of access rights, Human error, UI design that is difficult to understand, Power outages, Network connection problems, Hacking, Data theft/hardware), Risk escalation (Trouble web server, Server down), Avoiding risks (Hardware damage, Data corrupt), Accepting risks (Earthquake, Flood). This research is expected to help UPC Pegadaian Ratahan to minimize the risks that may occur in the future.